Effect of Capital Adequacy Ratio, Credit Policy, Liquidity Risk and Non-Performing Loan on Financial Distress - Indra Wahyu Putra, Christophorus; Haymans Manurung, Adler; Marinda Machdar, Nera (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this literature research is to build hypotheses regarding the influence between variables which can later be used for further research in financial management. The literature review research article on the effect of Capital Adequacy Ratio, Credit Policy, Liquidity Risk, and Non-Performing Loans on Financial Distress is a scientific literature article within the scope of financial management science. The approach used in this literature review research is descriptive qualitative. The data collection technique uses literature studies or reviews relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and comes from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Capital Adequacy Ratio affects Financial Distress; 2) Credit Policy affects Financial Distress; 3) Liquidity Risk affects Financial Distress; and 4) Non-Performing Loan affects Financial Distress.